2007
DOI: 10.1136/ard.2007.077693
|View full text |Cite
|
Sign up to set email alerts
|

The Wegener's granulomatosis quantitative trait locus on chromosome 6p21.3 as characterised by tagSNP genotyping

Abstract: The HLA-DPB1/RING1 region is strongly associated with WG in ANCA-positive subjects. Further analyses of potential cis regulatory sequences of candidate genes HLA-DPB1, RING1 and RXRB appear warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
62
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 33 publications
5
62
1
3
Order By: Relevance
“…A number of studies have shown an association of HLA genes, including both class I and class II, with the disease susceptibility of AAV (8)(9)(10)(11)(12)(13)(14). There are five loci of MHC class II genes in HLA, including HLA-DR, HLA-DP, HLA-DQ HLA-DO, and HLA-DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown an association of HLA genes, including both class I and class II, with the disease susceptibility of AAV (8)(9)(10)(11)(12)(13)(14). There are five loci of MHC class II genes in HLA, including HLA-DR, HLA-DP, HLA-DQ HLA-DO, and HLA-DM.…”
Section: Introductionmentioning
confidence: 99%
“…Among the genetic factors, HLA genes are considered a set of suspected genes in the development of AAV (8)(9)(10)(11)(12)(13)(14). A number of studies have shown an association of HLA genes, including both class I and class II, with the disease susceptibility of AAV (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…A major genomic risk locus for WG has been identified on chromosome 6p21.3 including the HLA-DPB1 gene. 6,7,8 Another HLA locus, HLA-DR, has also been linked to WG susceptibility. 9,10 Other genetic risk factors for WG comprise a polymorphism in PTPN22, 11 which has been identified as a risk factor in different (auto)-immune disorders, and variations in the a1-antitrypsin gene.…”
Section: Introductionmentioning
confidence: 99%
“…Research is being carried out to confirm this association, for instance, to confirm the possible relation between WG and a region on chromosome 6p21.3 (11) , although further investigation is needed. Indeed, this autoimmune disease is genetically associated with the class II region of the major www.intechopen.com histocompatibility complex (MHC), such as HLA-DPB1*0401 allele (12,13) . Similarly to other autoimmune diseases, the functional polymorphism, 620W, in the intracellular tyrosine phosphatase gene PTPN 22, is a predisposing factor for WG in the presence of ANCA.…”
mentioning
confidence: 99%